2018
DOI: 10.1590/s1983-41952018000600008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the assessment methods of reinforced concrete beams in fire conditions proposed by NBR 15200

Abstract: In Brazil, reinforced concrete structures designed based on NBR 6118 [1] must be assessed in fire conditions through NBR 15200 [2], which proposes multiple test methods. Concerning beams, this standard offers the tabular and simplified methods as possible choices. This study aimed to compare these two methods by applying their principles to isostatic and hyperstatic beams with section of 20x50 cm, designed at room temperature according to NBR 6118 [1]. The temperature distribution along sections was obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
(14 reference statements)
0
5
0
3
Order By: Relevance
“…In this analysis, the closest reinforcement to the heated face was considered. It is worth mentioning that this is a foundation of the tabular method along with width beams and level load (Bolina et al. , 2018; Silva, 2011).…”
Section: Parametric Analysis Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this analysis, the closest reinforcement to the heated face was considered. It is worth mentioning that this is a foundation of the tabular method along with width beams and level load (Bolina et al. , 2018; Silva, 2011).…”
Section: Parametric Analysis Resultsmentioning
confidence: 99%
“…The study showed that hyperstatic beams had gains of up to 30 min in fire resistance time compared to isostatic beams. Furthermore, in the analyzed cases, the tabular method resulted in TRRF values higher than the verified TRFs (Bolina et al. , 2018).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations